Plasma Albumin Redox State Is Responsive to the Amino Acid Balance of Dietary Proteins in Rats Fed a Low Protein Diet - Wada, Yasuaki; Xijier,; Seto, Namiko; Komatsu, Yosuke; Tsuda, Muneya; Kitamura, Yohei; Izumi, Hirohisa; Shimizu, Takashi; Takeda, Yasuhiro (Frontiers in Nutrition, 2019)
We recently reported that plasma albumin redox state, which correlates with albumin synthesis rate, could be associated with the quality of dietary protein. Aiming to elucidate the association between them, plasma albumin redox state was investigated in rats fed various kinds of AIN-93G-based low protein diets. Plasma albumin redox state was shifted to a more oxidized state in rats fed 3% casein (CN) diet than those fed 3% whey protein or 3% wheat gluten diet, while supplementing 3% CN diet with cystine reversed it to a more reduced state, indicating that cystine would complement the shortage of cysteine in CN, thereby increasing albumin synthesis rate. Supplementation with glutathione, a cysteine-containing antioxidative tripeptide, normalized hepatic glutathione redox state modulated by ingestion of 3% CN diet, but it only reversed the oxidized shift of plasma albumin redox state to an extent similar to cystine alone or the constituting amino acid mixture of glutathione (i.e., glutamic acid, cystine, and glycine), indicating that glutathione would primarily serve as a source of cysteine rather than exert its antioxidative activity. Plasma albumin would thus be influenced by amino acid balance in dietary proteins, and it could be useful as a biomarker that contributes to prevention of protein under-nutriton, accompanied by not only insufficient protein intake but also ingestion of poor-quality protein.